¿Sexualidad en disputa? El reggaetón cantado por mujeres - Diaz Saenz, Lucia Cristina (2025)
This article analyzes representations of female sexuality in reggaeton songs performed by women. Based on an analysis of a corpus of popular songs on streaming platforms and social media in Latin America, it explores narratives about female sexual pleasure, autonomy, and the tensions between subversion and reproduction of patriarchal norms. The conclusions highlight how artists reconfigure their role as desiring subjects and generate new representations of desire and pleasure. However, female reggaeton, although presented as a means of empowerment and sexual liberation, also shows contradictions by simultaneously reproducing patriarchal stereotypes. This highlights the duality of gender as a space where subversion and the perpetuation of traditional norms coexist, emphasizing its complexity as a terrain of cultural and symbolic dispute around female sexuality.